Numerical Solution of Continuation Problem for 3D Steady-State Diffusion in Cylindrically Layered Medium - Magira Kulbay; Saule Maussumbekova; Balgaisha Mukanova (Abstract and Applied Analysis)
This work is based on the application of Fourier and quasi-solution methods for solving the continuation inverse problem for 3D steady-state diffusion model inside a cylindrical layered medium. The diffusion coefficient is supposed to be a piecewise constant function, Cauchy data are given on the outer boundary of the cylinder, and we seek to recover the temperature at the inner boundary of the cylinder. Numerical experiments are investigated and show the capacity of proposed method only for smooth boundary condition. Under the suitable choice of regularization parameters we recover the distribution of temperature on the inner boundary with satisfactory quality for noisy data.